Biodistribution and first clinical results of 18F-SiFAlin-TATE PET: a novel 18F-labeled somatostatin analog for imaging of neuroendocrine tumors - Ilhan, Harun; Lindner, S.; Todica, A.; Cyran, C. C.; Tiling, R.; Auernhammer, C. J.; Spitzweg, C.; Boeck, S.; Unterrainer, M.; Gildehaus, F. J.; Böning, G.; Jurkschat, K.; et al. (European journal of nuclear medicine and molecular imaging, 2020)
PET/CT using 68Ga-labeled somatostatin analogs (SSA) targeting somatostatin receptors (SSR) on the cell surface of well-differentiated neuroendocrine tumors (NET) represents the clinical reference standard for imaging. However, economic and logistic challenges of the 68Ge/68Ga generator-based approach have disadvantages over 18F-labeled compounds. Here, we present the first in-human data of 18F-SiFAlin-TATE, a novel 18F-labeled, SSR-targeting peptide. The aim was to compare the intra-individual biodistribution, tumor uptake, and image quality of 18F-SiFAlin-TATE to the clinical reference standard 68Ga-DOTA-TOC.
Gesehen am 23.06.2020
Published online: 6 September 2019